Formulation and Evaluation Of Dextromethorphan Hydrobromide Soft Gelatin Capsules - Mittal, Priyanka; Soni, Shankar; Khinchi, M. P (Asian Journal of Pharmaceutical Research and Development, 2015)
The present study provides a new composition for treating cough, comprising dextromethorphan HBr . In the present work the soft gelatin capsules were formulated comprising 15mg dextromethorphan HBr using PEG 400, PG , PVP k-30 and purified water. The prepared soft gelatin capsules were evaluated for weight variation test, assay, dissolution and disintegration. The capsules had a fill weight of 400 ± 5%, Disintegration time of 8 -10 minutes and showed 97.00% to 99.50% of labelled amount of dextromethorphan HBr indicating uniformity in drug contents. The capsules containing 335 mg/capsule of propylene glycol released 100.07% of dextromethorphan HBr at the end of 9 minutes. Thus, it may be concluded that soft gelatin capsules of dextromethorphan HBr could be successfully prepared with existing technology and machinery which have a commercial viability and enhance patient compliance with improved bioavailability